Prognostic and diagnostic significance of circRNAs expression in hepatocellular carcinoma patients: A meta‐analysis - Xin Huang; Weiyue Zhang; Zengwu Shao (Cancer Medicine)
Abstract Circular RNAs (circRNAs) as novel biomarkers are widely investigated in various cancers. The aim of our study was to reveal the clinicopathological, prognostic, and diagnostic features of circRNAs in human hepatocellular carcinoma (HCC). A systematical search was conducted on PubMed, Scopus, Web of Science (WOS), EMBASE, and the Cochrane Library databases. Eligible studies reporting on the association among circRNAs and clinicopathological, prognostic, diagnostic values of HCC patients were included. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were utilized to assess clinicopathological parameters, sensitivity, and specificity, and hazard ratios (HRs) were to evaluate overall survival (OS). 17 eligible studies which included 7 for clinicopathological features, 10 for prognosis, and 8 for diagnosis were in our study. As for clinicopathological parameters, high expression of oncogenic circRNAs had a significant association with poor clinicopathological features and tumor‐suppressor circRNAs proved the contrary. In terms of the prognostic values, oncogenic circRNAs had a negative influence on overall survival (OS: HR = 3.39, 95%Cl: 2.59‐4.19), and high expression of tumor‐suppressor circRNAs was relevant to improved survival outcomes (OS: HR = 0.46, 95%Cl: 0.37‐0.56). The pooled diagnostic outcomes indicated an area under the curve (AUC) of 0.84, with sensitivity of 82% and specificity of 72% in discriminating HCC from controls. Our study indicates that circRNAs may be important biomarkers for prognostic and diagnostic values of HCC.